Compact electron spin resonance skin oximeter: Properties and initial clinical results - Cristea, David; Wolfson, Helen; Ahmad, Rizwan; Twig, Ygal; Kuppusamy, Periannan; Blank, Aharon (Magnetic resonance in medicine, 2021)
Purpose Skin oxygen level is of significance for the diagnosis and treatment of many clinical problems, such as chronic wounds and diabetic foot ulcers. Furthermore, skin oxygen levels can be correlated to arterial oxygen partial pressure, thereby revealing potentially dangerous conditions such as hyperoxia (too much oxygen), which may occur in ventilated neonates. Traditionally, skin oxygen levels are measured using electrochemical methods and, more recently, also by fluorescence lifetime techniques. These approaches suffer from several drawbacks, rendering them suboptimal. The purpose of this work is to develop an electron spin resonance (ESR) ‐based method for monitoring oxygen partial pressure (pO2) in skin tissue. Methods A compact sensor for pulsed ESR is designed and constructed. Our ESR‐based method makes use of a unique exogenous paramagnetic spin probe that is placed on the skin in a special partially sealed sticker, and subsequently measuring its signal with the compact pulsed ESR sensor that includes a miniature magnet and a small S‐band (~2.3 GHz) microwave resonator. The inverse of the spin‐spin relaxation time (1/T2) measured by ESR is shown to be linearly correlated with pO2 levels. Results The sensor and its matching sticker were tested both in vitro and in vivo (with human subjects). Measured skin pO2 levels reached equilibrium after ~2‐3 h and were found to be comparable to those measured by continuous‐wave (CW) ESR using a large electromagnet. Conclusions A compact pulsed ESR sensor with a matching paramagnetic sticker can be used for pO2 monitoring of the skin tissue, similar to large bulky CW ESR systems.